PEMBUATAN PUPUK ORGANIK CAIR DARI URINE SAPI DENGAN VARIASI JENIS BIOAKTIVATOR - Firda Anisa; Fitriyana Fitriyana; Noorma Kurnyawaty (Politeknik Negeri Samarinda, 2021)
Cow urine is one of the waste materials or the results of the excretion system of cow metabolism that greatly interferes with the community around the farm if not processed properly. Cow urine in general contains macro nutrients, including: 1.4 - 2.2% Nitrogen, 0.6 - 0.7% Phosphorus, 1.6 - 2.1% Potassium, and C-organic, so that cow urine can be used as a liquid organic fertilizer in order to become a more useful agricultural product. This study aims to find out the best bioactivator for the manufacture of Liquid Organic Fertilizer (POC) from cow urine. The manufacture of liquid organic fertilizer from cow urine can be done by fermentation method. The fermentation process was carried out for 14 days in a closed state with variations in the types of bioactivators used namely EM4, Promi, Orgadec, Stardec and Petrofast. Bioactivators were used to speed up the process of decomposing and remodeling organic matter from cow urine. From the results of the analysis conducted, the best bioactivator was stardec bioactivators with N content of 0.07%, P of 0.016%, K of 0.478%, C-organic of 1.27% and pH of 4.90.